The Influence of Children's Playground Facilities on Visiting Decisions and Visit Motivation as a Moderation Variable in City Parks in the City of Jakarta (Case Study: Taman Sambas Asri Blok M, Taman Puring Jakarta, and Tebet Eco Park) - Oktavia, Reno Catelya Dira; Amrullah, Amrullah; Oktovianus, Oktovianus (Jurnal Penelitian Pariwisata, 2025)
This research aims to analyze the influence of children's playground facilities on visiting decisions, with visiting motivation as a moderation variable. Good playground facilities can improve the experience and comfort of visitors, which ultimately influences the decision to visit again. This research uses a quantitative approach with data analysis through the Structural Equation Modeling (SEM) method using Smart PLS software. Respondents for this study consisted of 215 people who visited city parks in the Jabodetabek area using purposive sampling. The research results show that (1) Children's playground facilities have a significant influence on visiting motivation and visiting decisions; (2) Motivation to visit also has a significant influence on the decision to visit; (3) The indirect influence of children's playground facilities on the decision to visit through visiting motivation is also significant. In conclusion, children's playground facilities are essential in increasing visiting decisions directly and indirectly through visiting motivation. Researchers suggest that city park managers pay attention to the quality and diversity of existing facilities to improve visitor experiences and encourage more frequent and sustainable visits. Keywords: children's playground facilities, visiting motivation, visiting decision